Remoção de nitrito, nitrato e amônia de efluentes de indústrias petrolíferas através de reatores biológicos inoculados com “Aspergillus niger” - Freitas Neto, Mário de Alencar (2005)
The purpose of this research was to evaluate the removal of nitrogen compounds found in petroleum industry wastewater, by employing a biologic process with fungi. During 156 days, two aerobic biologic reactors with fungi (BRF), with immobilized biomass and continuous up flow were built and operated. Both reactors were made in acrylic and presented identical dimensions height 60 cm, 10 cm diameter and 4,5 L liquid volume. The first reactor (R1) had polyamide bed as support medium and the second one (R2) used polyurethane foam. Initially, the reactors containing the wastewater were inoculated with 2 x 106 spores.mL-1, of Aspergillus niger AN 400. They remained in rest, with no aeration, for 24 h mycelium growth. After this period, the aeration and recirculation of the effluent started and here mointained for one week. The recirculation was then suspended and it was initiated the reactors feeding with wastewater and the parameters monitoring. The research was divided in four phases, with different HRT and different glucose concentrations (except phase I) as primary source of carbon. In phase I, the reactors were operated for 35 days with 8h HRT and with no addition of primary source of carbon. Good nitrite removal efficiencies were observed, with mean values of 82% and 89%, for R1 and R2, respectively. For nitrate, the mean values were 53% for R1 and 55% for R2. In relation to ammonia, the mean values in effluent concentration were: R1, 10,31 mg N-NH3.L-1 and R2, 10,62 mg N-NH3.L-1, which were higher than the affluent values, with a mean value of 7,87 mg N-NH3.L-1. In phase II, the reactors were operated for 59 days with HRT of 8h and 0,5 g/L of glucose were added to the affluent. The mean values of ammonia removal were 57% for R1 and 51% for R2. Nitrite, values were 82% and 84% for R1 and R2 respectively, nitrate 70% for R1 and 80% for R2. In phase III, the HRT was reduced to 4h and the addition of glucose was sustained. In this phase, the reactors were operated for 38 days. The removal values observed for ammonia were 54% for R1 and 57% and R2. In relation to nitrite, these values were 90% and 76% for R1 and R2 respectively and for nitrate the values were 63% and 62% for R1 and R2. In phase IV, reactors were operated for 24 days, with HRT of 4h and addition of 1,0 g.L-1 of glucose to the affluent. The removal values obtained for ammonia were 48% and 53% for R1 and R2, and for nitrate these values were 76% and 79% for R1 and R2. In relation to nitrite, the mean value of the effluent was 0,04 mg N-NO2.L-1 for both reactors, twice the value of the affluent (0,02 mg N-NO2.L-1). In this research, it was observed an alternation between production and removal of ammonia and nitrite however the reactors when operated in phase II and III showed efficient in the removal of nitrite, nitrate and ammonia present in petroleum industry wastewater.